Assessment of testing methods for higher temperature performance of emulsified asphalt. (15th November 2022) - Wang, Decai; Hu, Lei; Dong, Shi; You, Zhanping; Zhang, Qing; Hu, Shengneng; Bi, Jiefu
Abstract: High-temperature features are crucial for evaluating the performance of emulsified asphalt. As effective binders, evaporation residues directly determine the high-temperature performance of emulsified asphalt. This study aims to systematically investigate the laboratory preparation process for different emulsified asphalt evaporation residues (EAERs) and proposes appropriate testing and evaluation methods. First, emulsified asphalt was prepared using five different material samples (cations M, A, L, T, and latex). Secondly, three evaporation methods were used to obtain EAERs: the direct heating method, low-temperature evaporation method, and improved evaporation method. Then, the high-temperature rheological parameters were determined using the Brookfield viscosity test, temperature-sweep test, and multiple stress creep recovery tests. Finally, microscopic test methods were adopted for the mechanism analysis, including the fourier transform infrared spectroscopy (FTIR) and the atomic force microscopy (AFM). The results show that different evaporation methods can significantly affect the high temperature performance evaluation results of EAERs. These differences are more obvious between high temperature evaporation and low temperature evaporation conditions. Moreover, the rutting resistance factor and phase angle of styrene-butadiene rubber (SBR) modified emulsified asphalt residues prepared by direct heating method present completely different change laws. From the FTIR and the AFM tests, it is found that these different change laws are due to the chemical reaction during the preparation of SBR modified emulsified asphalt residue by direct heating, which may be the aging of material or the degradation of polymer. In conclusion, the low-temperature evaporation method is recommended to prepare EAERs for a more realistic evaluation of the high-temperature performance of emulsified asphalt. The improved evaporation method should be prioritized as it further standardizes the parameters for subsequent laboratory testing. Graphical abstract: Image 1 Highlights: Study the influence of evaporation method on the residue test results simultaneously. Propose the testing and evaluation parameters of evaporation residues systematically. Reveal the mechanisms of action and internal reasons through the FTIR and AFM.